2022
DOI: 10.1101/2022.08.12.503665
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Somatic and terminal CB1 receptors are differentially coupled to voltage-gated sodium channels in neocortical neurons

Abstract: Endogenous cannabinoid signaling is vital for important brain functions and can be modified pharmacologically to treat pain, epilepsy, and posttraumatic stress disorder. Endocannabinoid mediated changes to excitability are predominantly attributed to 2-arachidonoylglycerol at synapses. Here we identify a pathway in the neocortex by which anandamide, the other major endocannabinoid, powerfully inhibits sodium conductances in the soma resulting in a loss of neuronal excitability. This pathway is mediated by the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…The evidence of an increased neuronal excitability seen in electrophysiological studies in the hippocampus may be related indirectly to this CB 1 downregulation. Indeed, it has been recently demonstrated that, in neocortical neurons, the activation of CB 1 receptors inhibits voltage gated sodium channels, reducing with high efficacy the neuronal excitability (Steiger et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of an increased neuronal excitability seen in electrophysiological studies in the hippocampus may be related indirectly to this CB 1 downregulation. Indeed, it has been recently demonstrated that, in neocortical neurons, the activation of CB 1 receptors inhibits voltage gated sodium channels, reducing with high efficacy the neuronal excitability (Steiger et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The protocol below has been developed and optimized for bouton recordings in mouse primary neocortical neuron-glia co-cultures (referred to as neocortical cultures below). 1 , 2 We first describe preparatory steps for bouton recordings, including the required equipment and solutions. Subsequently, we describe how low-capacitance quartz glass pipettes are manufactured, which are optimally suited for bouton recordings.…”
Section: Before You Beginmentioning
confidence: 99%
“…Finally, we describe errors related to pipette capacitance and how to achieve optimal pipette capacitance compensation required for high-resolution bouton recordings. We have successfully used this protocol for bouton recordings in mouse primary neocortical cultures and rat acute neocortical brain slices 1 , 2 and for dopaminergic axon recordings in rat acute striatal brain slices. 3 Furthermore, we are currently adapting this protocol for bouton recordings in rat hippocampal cultures and human iPSC-derived neuronal cultures.…”
Section: Before You Beginmentioning
confidence: 99%